On mean labeling of some trees - Jeyanthi P.; Ramya D.; Maheswari A. (Utilitas Mathematica, 2014)
Let G be a (p, q) graph and f: V(G)→0,1,2,3,..., q be an injection. For each edge e = uv, let f*(e) = [f(u)+f(v)/2] .then f is called a mean labeling if f*(e): e ε E (G) = 1, 2, 3,..., q. A graph that admits a mean labeling is called a mean graph. In this paper, we prove <P2môK1,n > , Tp-tree and TO K n, where T is a Tp-tree, are mean graphs.